Laser reflecting film system as well as preparation method and application thereof
By adopting a specific film system structure and vacuum electron beam evaporation coating technology, a laser reflective film with high reflectivity, strong adhesion and good friction resistance are prepared, which solves the problem of insufficient performance of the laser reflective film in the prior art.
Patent Information
- Application Number
- CN202411852975.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-16
AI Technical Summary
It is difficult to prepare a full-die laser reflective film that has both a high laser damage threshold and can meet high laser beam quality, and the adhesion, moderate friction resistance and constant temperature and humidity performance of the film layer are insufficient.
The film system structure of Sub/0.5L (H0.5L)^4(G0.5L)^2(M0.5L)^3/Air is adopted, wherein the low refractive index layer is SiO2, the first high refractive index layer is Ta2O5, the second high refractive index layer is Ti3O5, the medium refractive index layer is HfO2, and the base material is quartz, which is prepared by vacuum electron beam evaporation coating technology.
It has achieved high reflectivity (reflectivity higher than 99%), high viscosity, good resistance to moderate friction and constant temperature and humidity, and has excellent anti-laser loss performance, which is suitable for high-reflection films of laser elements.
Smart Images

Figure CN119596432A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of laser film system structure, and specifically relates to a high-reflective film used in laser elements after laser film coating, and a design and preparation method of a thin film with anti-laser damage threshold in the film system structure during the use of laser equipment. Background Art
[0002] As the requirements for laser output light power and spot quality in industry (laser marking machine, laser cutting machine), medical laser instruments and military are constantly increasing, the damage threshold and surface shape of laser cavity mirror high reflection film have been put forward. How to prepare all-medium laser reflection film with high laser damage threshold and high laser beam quality has become a hot topic for domestic and foreign scholars, and it is also the goal pursued by optical coating companies. Most companies and research institutions use the method of electron gun thermal evaporation. The film layer coated by this method is relatively loose and has serious surface defects. A few companies use ion beam sputtering (IBS) coating, but the stress is large, resulting in large changes in surface shape, and the output spot quality does not meet the use requirements. Some companies and institutions use the method of post-treatment after plating to increase the damage threshold, but the threshold is not significantly increased, and the surface shape does not change much by releasing stress through heating. There will be rebound as the use time increases. To design and prepare high-quality, highly reflective films for laser systems, not only the spectral characteristics must be considered, but also the film's ability to resist laser damage. Laser films have very strict requirements on material density. In addition, they must also meet film adhesion, moderate friction resistance, and constant temperature and humidity requirements. Summary of the invention
[0003] In response to the above technical problems, the present application provides a laser reflective film system and a preparation method and application thereof.
[0004] To achieve the above objectives, this application proposes the following technical solutions: In a first aspect, a laser reflective film system is provided, comprising a substrate and a film system structure symmetrically arranged on both sides of the substrate, wherein the film system structure is Sub / 0.5L(H0.5L)^4(G0.5L)^2(M0.5L)^3 / Air, wherein Sub is the substrate, Air is the emitting medium air, L represents a low refractive index layer of a basic thickness, H represents a first high refractive index layer of a basic thickness, G represents a second high refractive index layer of a basic thickness, and M represents a medium refractive index layer of a basic thickness, wherein the basic thickness corresponding to 1 H or 1 L or 1 G or 1 M represents that the film layer has a 1 / 4 optical thickness at a reference wavelength.
[0005] Furthermore, the low refractive index layer is a SiO2 layer, the first high refractive index layer is a Ta2O5 layer, the second high refractive index layer is a Ti3O5 layer, and the medium refractive index layer is a HfO2 layer.
[0006] Furthermore, the substrate is made of quartz.
[0007] Furthermore, the reflectivity of the laser reflective film system to light with a wavelength of 355 nm is greater than 99%.
[0008] Further, the film structure includes a first SiO2 layer, a first Ta2O5 layer, a second SiO2 layer, a second Ta2O5 layer, a third SiO2 layer, a third Ta2O5 layer, a fourth SiO2 layer, a fourth Ta2O5 layer, a fifth SiO2 layer, a first Ti3O5 layer, a sixth SiO2 layer, a second Ti3O5 layer, a seventh SiO2 layer, a first HfO2 layer, an eighth SiO2 layer, a second HfO2 layer, a ninth SiO2 layer, a third HfO2 layer and a tenth SiO2 layer, which are sequentially arranged on the surface of the silicon substrate; the thickness of the first SiO2 layer is 42-44 nm, the thickness of the first Ta2O5 layer is 40.5-42.5 nm, the thickness of the second SiO2 layer is 38.5-40.5 nm, the thickness of the second Ta2O5 layer is 26.5-28.5 nm, the thickness of the third SiO2 layer is 50.5-52.5 nm, the thickness of the third Ta2O5 layer is 10 The thickness of the fourth SiO2 layer is 78.5~80.5nm, the thickness of the fourth Ta2O5 layer is 46.5~48.5nm, the thickness of the fifth SiO2 layer is 68.5~70.5nm, the thickness of the first Ti3O5 layer is 86.5~88.5nm, the thickness of the sixth SiO2 layer is 68.5~70.5nm, the thickness of the second Ti3O5 layer is 11.3~13.5nm, the thickness of the seventh SiO2 layer is 41.5~43.5nm, the thickness of the first HfO2 layer is 49.5~51.5nm, the thickness of the eighth SiO2 layer is 63.5~65.5nm, the thickness of the second HfO2 layer is 68.5~70.5nm, the thickness of the ninth SiO2 layer is 77~79nm, the thickness of the third HfO2 layer is 57~59nm, and the thickness of the tenth SiO2 layer is 160~163nm.
[0009] Furthermore, the thickness of the first SiO2 layer is 43 nm, the thickness of the first Ta2O5 layer is 41.42 nm, the thickness of the second SiO2 layer is 39.41 nm, the thickness of the second Ta2O5 layer is 27.46 nm, the thickness of the third SiO2 layer is 51.62 nm, the thickness of the third Ta2O5 layer is 47.47 nm, the thickness of the fourth SiO2 layer is 79.7 nm, the thickness of the fourth Ta2O5 layer is 47.47 nm, the thickness of the fifth SiO2 layer is 69.72 nm, the thickness of the first Ti3 The thickness of the O5 layer is 87.46nm, the thickness of the sixth SiO2 layer is 69.72nm, the thickness of the second Ti3O5 layer is 12.34nm, the thickness of the seventh SiO2 layer is 42.5nm, the thickness of the first HfO2 layer is 50.71nm, the thickness of the eighth SiO2 layer is 64.4nm, the thickness of the second HfO2 layer is 69.67nm, the thickness of the ninth SiO2 layer is 77.91nm, the thickness of the third HfO2 layer is 57.92nm, and the thickness of the tenth SiO2 layer is 161.5nm In a second aspect, a method for preparing the aforementioned laser reflective film system is provided, comprising: Plating a film layer on the first surface of the substrate according to the film system structure on the first surface of the substrate; Plating a film layer identical to that on the first surface on the second surface of the substrate; After cooling to room temperature, the laser reflective film system is obtained.
[0010] Furthermore, before the film layer on the first surface and the film layer on the second surface of the substrate are plated, the process includes: placing the substrate in a coating machine, evacuating the vacuum to 2.0×10 -3 ±0.5×10 -3 Pa, preheat to 115~125℃, and clean the ion source.
[0011] Furthermore, the plating temperature of each film layer is 115~125℃.
[0012] Furthermore, the vacuum degree in the cavity during the deposition of each film layer is 2.0×10 -3 ±0.5×10 -3 Pa.
[0013] Furthermore, the deposition rate of the SiO2 layer is 7.6~8.8Å / s; the deposition rate of the Ta2O5 layer is 4.5~5.5Å / s; the deposition rate of the Ti3O5 layer is 3~4Å / s; and the deposition rate of the HfO2 layer is 3.5~4.5Å / s.
[0014] Furthermore, each film layer is deposited by vacuum electron beam evaporation.
[0015] Furthermore, after the coating is completed, it is first kept at 115~125℃ for 10~20min and then step-cooled to below 70℃ before being taken out.
[0016] Furthermore, the deposition of the SiO2 layer is carried out with the assistance of an RF ion source; the parameters of the RF ion source are: voltage of 800±5V, current of 800±5mA, ACC voltage of 600±5V, gas filling volume of oxygen 50±5sccm, and neutralizer argon 8±5sccm.
[0017] Furthermore, the deposition of the Ta2O5 layer is carried out with the assistance of an RF ion source; the parameters of the RF ion source are: voltage of 900±5V, current of 900±2mA, ACC voltage of 600±5V, gas filling volume of oxygen 50±5sccm, and neutralizer argon 8±5sccm.
[0018] Furthermore, the deposition of the Ti3O5 layer is carried out with the assistance of an RF ion source; the parameters of the RF ion source are: voltage of 800±5V, current of 800±5mA, ACC voltage of 600±5V, gas filling volume of argon 60±5sccm, and neutralizer argon 10±5sccm.
[0019] Furthermore, the deposition of the HfO2 layer is carried out with the assistance of an RF ion source; the parameters of the RF ion source are: voltage of 800±5V, current of 800±2mA, ACC voltage of 600±5V, gas filling volume of argon 50±5sccm, and neutralizer argon 8±5sccm.
[0020] In a third aspect, a laser is provided, comprising the aforementioned laser reflective film system or the laser reflective film system prepared by the aforementioned preparation method.
[0021] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects: The laser reflective film system provided has high reflectivity, good film layer adhesion, moderate friction resistance, good constant temperature and humidity resistance, and excellent anti-laser loss performance, and can be used as a high-reflective film for laser components.
[0022] The laser reflective film system provided has a high yield rate.
[0023] The provided coating structure design and preparation method are simple and easy to implement, and the reflectivity of the resulting high-reflective film is higher than 99%, and the yield is high. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 This is a high-reflection spectrum diagram of the laser reflective film system designed for Example 1.
[0026] Figure 2 This is the measured high-reflection spectrum of the laser reflective film system prepared in Example 1.
[0027] Figure 3 This is the measured high-reflection spectrum of the laser reflective film system prepared in Comparative Example 1.
[0028] Figure 4 This is the measured high-reflection spectrum of the laser reflective film system prepared in Comparative Example 3. DETAILED DESCRIPTION
[0029] Some embodiments of the present invention provide a laser reflective film system, including a film system structure symmetrically arranged on both sides of a substrate, wherein the film system structure is Sub / 0.5L(H0.5L)^4(G0.5L)^2(M0.5L)^3 / Air, that is, Sub / 0.5L(H0.5LH0.5LH0.5LH0.5L)(G0.5LG0.5L)(M0.5LM0.5LM0.5L) / Air, wherein Sub is the substrate, Air is the emitting medium air, L represents a low refractive index layer of a basic thickness, H represents a first high refractive index layer of a basic thickness, G represents a second high refractive index layer of a basic thickness, and M represents a medium refractive index layer of a basic thickness, wherein the basic thickness corresponding to 1 H or 1 L or 1 G or 1 M represents that the film layer has a 1 / 4 optical thickness at a reference wavelength.
[0030] In some preferred embodiments, the low refractive index layer is a SiO2 layer, the first high refractive index layer is a Ta2O5 layer, the second high refractive index layer is a Ti3O5 layer, and the medium refractive index layer is a HfO2 layer.
[0031] In some preferred embodiments, the substrate is made of quartz.
[0032] In some preferred embodiments, the average reflectivity of the laser reflective film system to light within a wavelength range of 355 nm is greater than 98%, preferably greater than 99%.
[0033] In some preferred embodiments, the film structure includes a first SiO2 layer, a first Ta2O5 layer, a second SiO2 layer, a second Ta2O5 layer, a third SiO2 layer, a third Ta2O5 layer, a fourth SiO2 layer, a fourth Ta2O5 layer, a fifth SiO2 layer, a first Ti3O5 layer, a sixth SiO2 layer, a second Ti3O5 layer, a seventh SiO2 layer, a first HfO2 layer, an eighth SiO2 layer, a second HfO2 layer, a ninth SiO2 layer, a third HfO2 layer and a tenth SiO2 layer, which are sequentially arranged on the surface of the silicon substrate; the thickness of the first SiO2 layer is 42-44 nm, the thickness of the first Ta2O5 layer is 40.5-42.5 nm, the thickness of the second SiO2 layer is 38.5-40.5 nm, the thickness of the second Ta2O5 layer is 26.5-28.5 nm, the thickness of the third SiO2 layer is 50.5-52.5 nm, the thickness of the third Ta2O5 layer is 51.5-53.5 nm, and the thickness of the third SiO2 layer is 50.5-51.5 nm. The thickness of the first SiO2 layer is 46.5~48.5nm, the thickness of the fourth SiO2 layer is 78.5~80.5nm, the thickness of the fourth Ta2O5 layer is 46.5~48.5nm, the thickness of the fifth SiO2 layer is 68.5~70.5nm, the thickness of the first Ti3O5 layer is 86.5~88.5nm, the thickness of the sixth SiO2 layer is 68.5~70.5nm, the thickness of the second Ti3O5 layer is 11.3~13.5nm, the thickness of the seventh SiO2 layer is 41.5~43.5nm, the thickness of the first HfO2 layer is 49.5~51.5nm, the thickness of the eighth SiO2 layer is 63.5~65.5nm, the thickness of the second HfO2 layer is 68.5~70.5nm, the thickness of the ninth SiO2 layer is 77~79nm, the thickness of the third HfO2 layer is 57~59nm, and the thickness of the tenth SiO2 layer is 160~163nm.
[0034] In some preferred embodiments, the thickness of the first SiO2 layer is 43 nm, the thickness of the first Ta2O5 layer is 41.42 nm, the thickness of the second SiO2 layer is 39.41 nm, the thickness of the second Ta2O5 layer is 27.46 nm, the thickness of the third SiO2 layer is 51.62 nm, the thickness of the third Ta2O5 layer is 47.47 nm, the thickness of the fourth SiO2 layer is 79.7 nm, the thickness of the fourth Ta2O5 layer is 47.47 nm, the thickness of the fifth SiO2 layer is 69.72 ... Ta2O5 layer is 41.42 nm, the thickness of the second SiO2 layer is 39.41 nm, the thickness of the second Ta2O5 layer is 27.46 nm, the thickness of the third SiO2 layer is 51.62 nm, the thickness of the third Ta2O5 layer is 47.47 nm, the thickness of the fifth SiO2 layer is 69.72 nm, the thickness of the first Ta2O5 layer is 41.42 nm, the thickness of the second Ta2O5 layer is 41.42 nm, the thickness of the second Ta2O5 layer is 41.42 nm, the thickness of the second Ta2O5 layer The thickness of the i3O5 layer is 87.46nm, the thickness of the sixth SiO2 layer is 69.72nm, the thickness of the second Ti3O5 layer is 12.34nm, the thickness of the seventh SiO2 layer is 42.5nm, the thickness of the first HfO2 layer is 50.71nm, the thickness of the eighth SiO2 layer is 64.4nm, the thickness of the second HfO2 layer is 69.67nm, the thickness of the ninth SiO2 layer is 77.91nm, the thickness of the third HfO2 layer is 57.92nm, and the thickness of the tenth SiO2 layer is 161.5nm.
[0035] The present invention also provides a method for preparing the aforementioned laser reflective film system, comprising: Plating a film layer on the first surface of the substrate according to the film system structure on the first surface of the substrate; Plating a film layer identical to that on the first surface on the second surface of the substrate; After cooling to room temperature, the laser reflective film system is obtained.
[0036] In some preferred embodiments, before the film layer on the first surface and the film layer on the second surface of the substrate are plated, the substrate is placed in a coating machine and vacuumed to 2.0×10 -3 ±0.5×10 -3 Pa, preheat to 115~125℃, and clean the ion source.
[0037] Before cleaning the ion source, the film material is pre-melted, degassed and impurities removed to ensure the purity of the film material.
[0038] Ion source ion cleaning can remove the oxide layer and attached particles on the surface of the product and the accompanying plated sheet, making the surface cleaner and increasing the adhesion of the film layer. The ion source can use an RF radio frequency source, and the parameters can be voltage 700±2V, current 700±2mA, ACC voltage 600±2V, gas filling volume 50±1sccm oxygen, 20sccm ion source argon, and 15ccm neutralizer argon.
[0039] In some preferred embodiments, the plating temperature of each film layer is 115-125°C.
[0040] In some preferred embodiments, the deposition rate of the SiO2 layer is 7.6~8.8Å / s; the deposition rate of the Ta2O5 layer is 4.5~5.5Å / s; the deposition rate of the Ti3O5 layer is 3~4Å / s; and the deposition rate of the HfO2 layer is 3.5~4.5Å / s.
[0041] In some preferred embodiments, each film layer is deposited by vacuum electron beam evaporation.
[0042] In some preferred embodiments, the deposition of the SiO2 layer is carried out with the assistance of an RF ion source; the parameters of the RF ion source are a voltage of 800±5V, a current of 800±5mA, an ACC voltage of 600±5V, a gas filling volume of 50±5sccm of oxygen, and a neutralizer argon gas of 8±5sccm.
[0043] In some preferred embodiments, the deposition of the Ta2O5 layer is carried out with the assistance of an RF ion source; the parameters of the RF ion source are a voltage of 900±5V, a current of 900±5mA, an ACC voltage of 600±5V, a gas filling volume of 50±5sccm of oxygen, and a neutralizer argon gas of 8±5sccm.
[0044] In some preferred embodiments, the deposition of the Ti3O5 layer is carried out with the assistance of an RF ion source; the parameters of the RF ion source are voltage of 800±5V, current of 800±5mA, ACC voltage of 600±5V, gas filling volume of argon 60±5sccm, and neutralizer argon 10±5sccm.
[0045] In some preferred embodiments, the deposition of the HfO2 layer is carried out with the assistance of an RF ion source; the parameters of the RF ion source are voltage of 800±5V, current of 800±5mA, ACC voltage of 600±5V, gas filling volume of argon 50±5sccm, and neutralizer argon 8±5sccm.
[0046] In some preferred embodiments, before placing the substrate into the coating machine, the substrate is polished and cleaned. Back reflection light is used to control and monitor the film thickness during the coating process.
[0047] In some preferred embodiments, after the coating on both sides of the substrate is completed, the substrate is taken out after being cooled down step by step to below 70°C. More preferably, after the coating is completed, the substrate is first kept at 115-125°C for 10-20 minutes and then cooled down step by step to below 70°C. Preferably, the step cooling is as follows: first, the substrate is cooled down to 95-105°C and kept for 5 minutes, then cooled down to 75-85°C and kept for 5 minutes, and finally cooled down to below 70°C and the door is opened for taking out.
[0048] The present invention also provides a laser, comprising the aforementioned laser reflective film system or the laser reflective film system prepared by the aforementioned preparation method.
[0049] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.
[0050] Example 1 The implementation process of the preparation method of the membrane structure disclosed this time is: The film system design uses 355nm as the central wavelength of the optical film design. The film stack formula is: Sub / 0.5L(H0.5L)^4(G0.5L)^2(M0.5L)^3 / Air, where Sub is the base material quartz, the base product is φ12.7*6.25mm, and the accompanying plating sheet is a quartz 77*77*0.5mm sheet. AIR represents air. In the film stack expression: L represents a low refractive index material SiO2 (silicon dioxide) with a thickness of 1 / 4 wavelength.
[0051] H represents high refractive index Ta2O5 (tantalum pentoxide) with a thickness of 1 / 4 wavelength.
[0052] G represents high refractive index Ti3O5 (titanium pentoxide) with a thickness of 1 / 4 wavelength.
[0053] M represents a medium refractive index material HfO2 (hafnium oxide) with a thickness of 1 / 4 wavelength.
[0054] After generation and optimization, the final film thickness is as follows, in nm: sub / SiO2(43) / Ta2O5(41.42) / SiO2(39.41) / Ta2O5(27.46) / SiO2(51.62) / Ta2O5(47.47) / SiO2(79.7) / Ta2O5(47.47) / SiO2(69.72) / Ti3O5( 87.46) / SiO2(69.72) / Ti3O5(12.34) / SiO2(42.5) / HfO2(50.71) / SiO2(64.4) / HfO2(69.67) / SiO2(77.91) / HfO2(57.92) / SiO2(161.5) / AIR; Step 1: Input the film thickness into the coating file, and set the coating temperature, evaporation rate, coating vacuum, ion source voltage, current, gas volume and other parameters.
[0055] Step 2: Clamp the pre-cleaned product and the accompanying plating sheet, then place them on the umbrella stand of the coating machine, close the door and exhaust the air, set the coating temperature to 120±2℃; the background vacuum before coating is 2.0×10 -3 ±0.1×10 -3Pa; Ta2O5 film deposition rate is 5±0.2Å / s; SiO2 film deposition rate is 8±0.2Å / s; Ti3O5 film deposition rate is 3.5±0.2Å / s; HfO2 film deposition rate is 4±0.2Å / s; Step 3: Pre-melt the film material to release air and remove impurities before coating to ensure the purity of the film material.
[0056] Step 4: The vacuum degree of the chamber reaches 2.0×10 -3 ±0.1×10 -3 Pa, start the RF source to ion clean the lens and the accompanying plating sheet, the cleaning time is 90±2s, the parameters are: voltage 700±2V, current 700±2mA, ACC voltage 600±2V, gas filling volume 50±1sccm of oxygen, 20sccm of ion source argon, and 15ccm of neutralizer argon.
[0057] Step 5: After the ion source is cleaned, call the coating process to start coating, and use back reflection light control to monitor the film thickness. When depositing the Ta2O5 film, the ion source parameters are: voltage 900±2V, current 900±2mA, ACC voltage 600±2V, gas filling volume 50±1sccm of oxygen, and neutralizer argon 8sccm. When depositing the SiO2 film, the ion source parameters are: voltage 800±2V, current 800±2mA, ACC voltage 600±2V, gas filling volume 50±1sccm of oxygen, and neutralizer argon 8sccm. When depositing the Ti3O5 film, the ion source parameters are: voltage 800±2V, current 800±2mA, ACC voltage 600±2V, gas filling volume 60±1sccm of argon, and neutralizer argon 10sccm. When depositing the HfO2 film, the ion source parameters are: voltage 800±2V, current 800±2mA, ACC voltage 600±2V, gas filling volume 50±1sccm of argon, and neutralizer argon 8sccm.
[0058] Step 6: Turn over the quartz glass substrate and the accompanying coating sheet and place them in the coating machine. Repeat steps 2 to 5 to coat the same film layer on the other surface (sub / SiO2(43) / Ta2O5(41.42) / SiO2(39.41) / Ta2O5(27.46) / SiO2(51.62) / Ta2O5(47.47) / SiO2(79.7) / Ta2O5(47.47) / SiO2(69.72) / Ti3O5(87.46) / SiO2(69.72) / Ti3O5(12.34) / SiO2(42.5) / HfO2(50.71) / SiO2(64.4) / HfO2(69.67) / SiO2(77.91) / HfO2(57.92) / SiO2(161.5) / AIR); Step 7: After coating, keep the temperature at 120±2℃ for 15 minutes, then step-down to 100±2℃ for 5 minutes, then to 80±2℃ for 5 minutes, and finally open the door to take out the parts when the temperature drops below 70±2℃.
[0059] After coating, the accompanying plate is subjected to spectrum test, and the durability test of quartz glass products is conducted: Constant temperature and humidity test: Double 85 test (tested at 85℃ and 85% humidity) for 36h, no quartz glass film was found to fall off or crack.
[0060] High and low temperature test: the temperature ranges from -40℃ to 71℃, and each gradient is kept warm for 2 hours. No film falling off or cracking on the surface of the quartz glass was found.
[0061] Moderate friction test: The film layer was rubbed 50 times with a rubber friction head wrapped with degreased cloth at a pressure of 4.9N, and no scratches or other damage were found.
[0062] Adhesion test: After each experiment, 3M tape was used to bond each side of the quartz glass and the tape was pulled in the direction opposite to the sticking end, but the film layer was not pulled up.
[0063] Laser light source use experiment: Installed in a 100W laser light source, the laser penetrates the surface of the film layer, and no damage or penetration marks are found on the film layer.
[0064] The high reflection spectrum of the designed laser reflective film system is shown in Figure 1 As shown, the measured high reflection spectrum is as follows Figure 2 shown.
[0065] Example 2 Step 1: Input the film thickness into the coating file, and set the coating temperature, evaporation rate, coating vacuum, ion source voltage, current, gas volume and other parameters.
[0066] Step 2: Clamp the pre-cleaned product and the accompanying plating sheet, then place them on the umbrella stand of the coating machine, close the door and exhaust the air, set the coating temperature to 118±2℃; the background vacuum before coating is 1.8×10 -3 ±0.1×10 -3 Pa; Ta2O5 film deposition rate is 4.8±0.2Å / s; SiO2 film deposition rate is 7.9±0.2Å / s; Ti3O5 film deposition rate is 3.3±0.2Å / s; HfO2 film deposition rate is 3.8±0.2Å / s; Step 3: Pre-melt the film material to release air and remove impurities before coating to ensure the purity of the film material.
[0067] Step 4: The vacuum degree of the chamber reaches 1.8×10 -3 ±0.1×10-3 Pa, start the RF source to ion clean the lens and the accompanying plating sheet, the cleaning time is 90±2s, the parameters are voltage 698±2V, current 698±2mA, ACC voltage 598±2V, the filling volume is oxygen 48±1sccm, ion source argon 20sccm, neutralizer argon 15ccm.
[0068] Step 5: After the ion source is cleaned, call the coating process to start coating, and use back reflection light control to monitor the film thickness. When depositing the Ta2O5 film, the ion source parameters are: voltage 898±2V, current 898±2mA, ACC voltage 598±2V, gas filling volume 48±1sccm of oxygen, and neutralizer argon 10sccm. When depositing the SiO2 film, the ion source parameters are: voltage 798±2V, current 798±2mA, ACC voltage 598±2V, gas filling volume 48±1sccm of oxygen, and neutralizer argon 10sccm. When depositing the Ti3O5 film, the ion source parameters are: voltage 798±2V, current 797±2mA, ACC voltage 598±2V, gas filling volume 58±1sccm of argon, and neutralizer argon 12sccm. When depositing the HfO2 film, the ion source parameters are: voltage 798±2V, current 798±2mA, ACC voltage 598±2V, gas filling volume 48±1sccm of argon, and neutralizer argon 10sccm.
[0069] Step 6: Turn over the quartz glass substrate and the accompanying coating sheet and place them in the coating machine. Repeat steps 3 to 6 to coat the same film layer on the other surface (sub / SiO2(43) / Ta2O5(41.42) / SiO2(39.41) / Ta2O5(27.46) / SiO2(51.62) / Ta2O5(47.47) / SiO2(79.7) / Ta2O5(47.47) / SiO2(69.72) / Ti3O5(87.46) / SiO2(69.72) / Ti3O5(12.34) / SiO2(42.5) / HfO2(50.71) / SiO2(64.4) / HfO2(69.67) / SiO2(77.91) / HfO2(57.92) / SiO2(161.5) / AIR); Step 7: After coating, keep the temperature at 120±2℃ for 15 minutes, then step-down to 100±2℃ for 5 minutes, then to 80±2℃ for 5 minutes, and then open the door to take out the parts when the temperature drops below 70℃.
[0070] Example 3 Step 1: Input the film thickness into the coating file, and set the coating temperature, evaporation rate, coating vacuum, ion source voltage, current, gas volume and other parameters.
[0071] Step 2: Clamp the pre-cleaned product and the accompanying plating sheet, then place them on the umbrella stand of the coating machine, close the door and exhaust, set the coating temperature to 122±2℃; the background vacuum before coating is 2.3×10 -3 ±0.1×10 -3 Pa; Ta2O5 film deposition rate is 5.2±0.2Å / s; SiO2 film deposition rate is 8.5±0.2Å / s; Ti3O5 film deposition rate is 3.6±0.2Å / s; HfO2 film deposition rate is 4.1±0.2Å / s; Step 3: Pre-melt the film material to release air and remove impurities before coating to ensure the purity of the film material.
[0072] Step 4: The vacuum degree of the chamber reaches 23×10 -3 ±0.1×10 -3 Pa, start the RF source to ion clean the lens and the accompanying plating sheet, the cleaning time is 90±2s, the parameters are: voltage 702±2V, current 702±2mA, ACC voltage 602±2V, gas filling volume 52±1sccm of oxygen, 20sccm of ion source argon, and 15ccm of neutralizer argon.
[0073] Step 5: After the ion source is cleaned, call the coating process to start coating, and use back reflection light control to monitor the film thickness. When depositing the Ta2O5 film, the ion source parameters are: voltage 902±2V, current 902±2mA, ACC voltage 601±2V, gas volume 52±1sccm of oxygen, and neutralizer argon 5sccm. When depositing the SiO2 film, the ion source parameters are: voltage 801±2V, current 801±2mA, ACC voltage 602±2V, gas volume 52±1sccm of oxygen, and neutralizer argon 6sccm. When depositing the Ti3O5 film, the ion source parameters are: voltage 802±2V, current 802±2mA, ACC voltage 602±2V, gas volume 62±1sccm of argon, and neutralizer argon 8sccm. When depositing the HfO2 film, the ion source parameters are: voltage 802±2V, current 802±2mA, ACC voltage 602±2V, gas filling volume 52±1sccm of argon, and neutralizer argon 5sccm.
[0074] Step 6: Turn over the quartz glass substrate and the accompanying coating sheet and place them in the coating machine. Repeat steps 3 to 6 to coat the same film layer on the other surface (sub / SiO2(43) / Ta2O5(41.42) / SiO2(39.41) / Ta2O5(27.46) / SiO2(51.62) / Ta2O5(47.47) / SiO2(79.7) / Ta2O5(47.47) / SiO2(69.72) / Ti3O5(87.46) / SiO2(69.72) / Ti3O5(12.34) / SiO2(42.5) / HfO2(50.71) / SiO2(64.4) / HfO2(69.67) / SiO2(77.91) / HfO2(57.92) / SiO2(161.5) / AIR); Step 7: After coating, keep the temperature at 123±2℃ for 15 minutes, then step-down to 103±2℃ for 5 minutes, then to 83±2℃ for 5 minutes, and finally open the door to take out the parts when the temperature drops below 70℃.
[0075] After many verifications, the laser film produced by the present invention has a strong film layer and strong laser resistance. The availability rate of 100 PCS of coated products is as high as 90%.
[0076] Example 4 The difference between this embodiment and embodiment 1 is that the evaporation rate of HfO2 is different, the evaporation rate is 5±0.2Å / S, and the rest remains unchanged.
[0077] Comparative Example 1 The difference between this comparative example and Example 1 is that the final film layer structure is different; the final film layer structures on both sides of the quartz substrate are as follows, in nm: sub / SiO2(34) / Ta2O5(57.42) / SiO2(59.98) / Ta2O5(37.68) / SiO2(60.02) / Ta2O5(37.65) / SiO2(60.04) / Ta2O5(37.65) / SiO2(100.04) / Ta2O5(3 7.64) / SiO2(60.04) / Ta2O5(37.65) / SiO2(60.04) / Ta2O5(37.65) / SiO2(60.03) / Ta2O5(59.65) / SiO2(59.98) / Ta2O5(37.68) / SiO2(60.42) / AIR.
[0078] Comparative Example 2 The difference between this comparative example and Example 1 is that the final film layer structure is different; the final film layer structures on both sides of the quartz substrate are as follows, in nm: sub / SiO2(70) / Ti3O5(66.31) / SiO2(120.46) / Ti3O5(31.46) / SiO2(59.23) / Ti3O5(31.29) / SiO2(61) / Ti3O5(30.74) / SiO2(64.85) / Ti3O5(39 .52) / SiO2(74.99) / Ti3O5(27.68) / SiO2(68.7) / HfO2(132.93) / SiO2(71.49) / HfO2(132.29) / SiO2(76.69) / HfO2(123.62) / SiO2(56.69) / AIR; Comparative Example 3 The difference between this comparative example and Example 1 is that the final film layer structure is different; the final film layer structures on both sides of the quartz substrate are as follows, in nm: sub / SiO2(60) / Ta2O5(43.2) / SiO2(23.5) / Ta2O5(53.87) / SiO2(35.48) / Ta2O5(67.09) / SiO2(28.67) / Ta2O5(45.90) / SiO2(34.76) / Ta2O5( 51.89) / SiO2(45.09) / Ta2O5(56.98) / SiO2(34.76) / HfO2(87.60) / SiO2(78.09) / HfO2(25.76) / SiO2(89.06) / HfO2(46.34) / SiO2(80) / AIR.
[0079] The spectra of the coated films of Examples 2 to 4 and Comparative Examples 1 to 3 were tested and the durability of the quartz glass products was tested. The test method was the same as that of Example 1. The results are shown in Table 1. The high reflection spectra of the films of Comparative Example 1 and Comparative Example 2 are shown in Table 1. Figure 3 , Figure 4 shown.
[0080] It can be seen from Table 1 that the reflectivity of the film system obtained in each embodiment at 355nm is above 99%, and the film layer has strong bonding strength, good constant temperature and humidity resistance, high and low temperature resistance, the film system is resistant to moderate friction, and the yield rate is above 80% under a 100W laser light source, among which the reflectivity of the film system obtained in Examples 1 to 3 is above 84%.
[0081] The reflectivity of the films obtained in Comparative Examples 1 to 3 at 355 nm is lower than 99%, and the film systems in Comparative Examples 1 and 2 have extremely low yields under a 100 W laser light source.
[0082] Table 1 The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A laser reflective film system, characterized in that: It includes a film structure symmetrically arranged on both sides of a substrate, wherein the film structure is Sub / 0.5L(H0.5L)^4(G0.5L)^2(M0.5L)^3 / Air, wherein Sub is the substrate, Air is the emitting medium air, L represents a low refractive index layer of a basic thickness, H represents a first high refractive index layer of a basic thickness, G represents a second high refractive index layer of a basic thickness, and M represents a medium refractive index layer of a basic thickness, wherein the basic thickness corresponding to 1 H or 1 L or 1 G or 1 M represents that the film layer has 1 / 4 optical thickness at the reference wavelength.
2. The laser reflective film system according to claim 1, characterized in that: The low refractive index layer is a SiO2 layer, the first high refractive index layer is a Ta2O5 layer, the second high refractive index layer is a Ti3O5 layer, and the medium refractive index layer is a HfO2 layer; The substrate is made of quartz.
3. The laser reflective film system according to claim 1, characterized in that: The reflectivity of the laser reflective film system to light with a wavelength of 355 nm is greater than 99%.
4. The laser reflective film system according to claim 2, characterized in that: The film system structure includes a first SiO2 layer, a first Ta2O5 layer, a second SiO2 layer, a second Ta2O5 layer, a third SiO2 layer, a third Ta2O5 layer, a fourth SiO2 layer, a fourth Ta2O5 layer, a fifth SiO2 layer, a first Ti3O5 layer, a sixth SiO2 layer, a second Ti3O5 layer, a seventh SiO2 layer, a first HfO2 layer, an eighth SiO2 layer, a second HfO2 layer, a ninth SiO2 layer, a third HfO2 layer and a tenth SiO2 layer which are sequentially arranged on the surface of the silicon substrate; the thickness of the first SiO2 layer is 42-44 nm, the thickness of the first Ta2O5 layer is 40.5-42.5 nm, the thickness of the second SiO2 layer is 38.5-40.5 nm, the thickness of the second Ta2O5 layer is 26.5-28.5 nm, the thickness of the third SiO2 layer is 50.5-52.5 nm, the thickness of the third Ta2O5 layer is 10. The thickness of the fourth SiO2 layer is 46.5~48.5nm, the thickness of the fourth Ta2O5 layer is 46.5~48.5nm, the thickness of the fifth SiO2 layer is 68.5~70.5nm, the thickness of the first Ti3O5 layer is 86.5~88.5nm, the thickness of the sixth SiO2 layer is 68.5~70.5nm, the thickness of the second Ti3O5 layer is 11.3~13.5nm, the thickness of the seventh SiO2 layer is 41.5~43.5nm, the thickness of the first HfO2 layer is 49.5~51.5nm, the thickness of the eighth SiO2 layer is 63.5~65.5nm, the thickness of the second HfO2 layer is 68.5~70.5nm, the thickness of the ninth SiO2 layer is 77~79nm, the thickness of the third HfO2 layer is 57~59nm, and the thickness of the tenth SiO2 layer is 160~163nm.
5. The laser reflective film system according to claim 4, characterized in that: The thickness of the first SiO2 layer is 43nm, the thickness of the first Ta2O5 layer is 41.42nm, the thickness of the second SiO2 layer is 39.41nm, the thickness of the second Ta2O5 layer is 27.46nm, the thickness of the third SiO2 layer is 51.62nm, the thickness of the third Ta2O5 layer is 47.47nm, the thickness of the fourth SiO2 layer is 79.7nm, the thickness of the fourth Ta2O5 layer is 47.47nm, the thickness of the fifth SiO2 layer is 69.72nm, and the thickness of the first Ti3O5 layer is 39.41nm. The thickness of the sixth SiO2 layer is 87.46nm, the thickness of the sixth SiO2 layer is 69.72nm, the thickness of the second Ti3O5 layer is 12.34nm, the thickness of the seventh SiO2 layer is 42.5nm, the thickness of the first HfO2 layer is 50.71nm, the thickness of the eighth SiO2 layer is 64.4nm, the thickness of the second HfO2 layer is 69.67nm, the thickness of the ninth SiO2 layer is 77.91nm, the thickness of the third HfO2 layer is 57.92nm, and the thickness of the tenth SiO2 layer is 161.5nm.
6. The method for preparing a laser reflective film system according to any one of claims 1 to 5, characterized in that: include: Plating a film layer on the first surface of the substrate according to the film system structure on the first surface of the substrate; Plating a film layer identical to that on the first surface on the second surface of the substrate; After cooling to room temperature, the laser reflective film system is obtained.
7. The method for preparing a laser reflective film system according to claim 6, characterized in that: Before coating the film layer on the first surface and the film layer on the second surface of the substrate, the process includes: placing the substrate in a coating machine, evacuating the vacuum to 2.0×10 -3 ±0.5×10 -3 Pa, preheat to 115~125℃, and clean the ion source.
8. The method for preparing a laser reflective film system according to claim 6, wherein: The plating temperature of each film layer is 115~125℃; The vacuum degree in the chamber during the deposition of each film layer is 2.0×10 -3 ±0.5×10 -3 Pa; The deposition rate of SiO2 layer is 7.6~8.8Å / s; the deposition rate of Ta2O5 layer is 4.5~5.5Å / s; the deposition rate of Ti3O5 layer is 3~4Å / s; the deposition rate of HfO2 layer is 3.5~4.5Å / s; Each film layer is deposited by vacuum electron beam evaporation coating; After coating is completed, keep it at 115~125℃ for 10~20min, then cool it down step by step to below 70℃ before taking it out.
9. The method for preparing a laser reflective film system according to claim 6, wherein: The deposition of the SiO2 layer is carried out with the assistance of an RF ion source; the parameters of the RF ion source are: voltage 800±5V, current 800±5mA, ACC voltage 600±5V, gas filling volume 50±5sccm of oxygen, and 8±5sccm of neutralizer argon; The deposition of the Ta2O5 layer was performed with the assistance of an RF ion source; the parameters of the RF ion source were: voltage 900±5V, current 900±2mA, ACC voltage 600±5V, gas filling volume 50±5sccm of oxygen, and 8±5sccm of neutralizer argon; The deposition of the Ti3O5 layer was performed with the assistance of an RF ion source; the parameters of the RF ion source were: voltage 800±5V, current 800±5mA, ACC voltage 600±5V, gas filling volume 60±5sccm of argon, and 10±5sccm of neutralizer argon; The deposition of the HfO2 layer is carried out with the assistance of an RF ion source; the parameters of the RF ion source are: voltage of 800±5V, current of 800±2mA, ACC voltage of 600±5V, gas filling volume of argon 50±5sccm, and neutralizer argon 8±5sccm.
10. A laser, characterized in that It comprises the laser reflective film system as described in any one of claims 1 to 5 or the laser reflective film system prepared by the preparation method as described in any one of claims 6 to 9.
Citation Information
Patent Citations
High-reflecting film and preparation method thereof
CN101806927A
High-reflection film for 10 kW semiconductor laser and preparation method thereof
CN110441844A
Combined reflecting film and preparation method thereof
CN113151783A
Laser protective film and production thereof
CN1439900A
Laser radar longitudinal scanning high-reflection film
CN217360287U